2021
DOI: 10.31234/osf.io/4bkwe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Defense of Natural Compatibilism

Abstract: In this chapter, I survey the experimental philosophy literature on folk intuitions about free will and moral responsibility. I argue that the hypothesis that folk are natural compatibilists is a better fit and explanation of existing data than the hypothesis that folk are natural incompatibilists. I discuss the use of 'Throughpass' measures in the recent literature (arguing that these measures are inadequate) as well as experimental philosophers' reliance on mediation analysis and structural equation modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…These results suggest that 1) more bypass judgments, 2) less desire to punish, and 3) introduction of a deterministic world via N&K scenarios consistently contributed to more incompatibilist responses. Intrusion judgment, however, less contributed to moral intuitions when simultaneously modeled with bypass and desire, challenging a relationship between intrusion and the increased compatibilist responses proposed by Nadelhoffer and colleagues (Nadelhoffer et al, 2020;2023). This inconsistency would be because of (1) the negative correlation between intrusion and bypass (Spearman's ρ = -.45 in the present sample) and (2) the fact that far fewer people have misunderstanding when it comes to intrusion compared with bypass.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…These results suggest that 1) more bypass judgments, 2) less desire to punish, and 3) introduction of a deterministic world via N&K scenarios consistently contributed to more incompatibilist responses. Intrusion judgment, however, less contributed to moral intuitions when simultaneously modeled with bypass and desire, challenging a relationship between intrusion and the increased compatibilist responses proposed by Nadelhoffer and colleagues (Nadelhoffer et al, 2020;2023). This inconsistency would be because of (1) the negative correlation between intrusion and bypass (Spearman's ρ = -.45 in the present sample) and (2) the fact that far fewer people have misunderstanding when it comes to intrusion compared with bypass.…”
Section: Resultscontrasting
confidence: 59%
“…The other was a deep attentional check intended to include only reliable data in our analyses. This was because a recent study by Florian Cova (2023) reported that many participants who passed surface attention checks failed deep attention checks. Importantly, we designed our deep attention check so that correct responses were on the left side of the 7-point scale.…”
Section: Deep Attentional Checkmentioning
confidence: 99%
“…However, Cova (2023) argues that it is unreasonable to expect that bypassing scores will fully explain incompatibilist intuitions, because bypass measures may not track bypass judgments with complete precision. It is possible for some participants to make bypass judgments and not agree with bypass statements, and for some participants to correctly understand determinism and mistakenly agree with bypass statements.…”
Section: Error Theories For Folk Intuitionsmentioning
confidence: 99%
“…Björnsson argues that individuals who agree with bypassing statements simply reject the idea that mental states have causal efficacy in an indeterministic sense. However, according to a recent study by Cova (2023) , people are unlikely to interpret bypassing statements in this way.…”
mentioning
confidence: 97%
“…In the past twenty years, experimental philosophers have been using experimental methods to get a better grasp at laypeople's intuitions about free will and moral responsibility (Nichols, 2011;Cova, 2023a). In most cases, these studies have investigated folk intuitions about free will and moral responsibility from the standpoint of the compatibility question: are free will and moral responsibility compatible with determinism?…”
Section: Introductionmentioning
confidence: 99%